2021
DOI: 10.1186/s12911-021-01513-x
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt (TIPS) procedure: an assessment of the quality and readability of online information

Abstract: Purpose Transjugular intrahepatic portosystemic shunt (TIPS) procedure is an established procedure carried out by interventional radiologists to achieve portal decompression and to manage the complications of portal hypertension. The aim of this study was to evaluate the quality and readability of information available online for TIPS procedure. Methods Websites were identified using the search terms “TIPS procedure”, “TIPSS procedure”, “transjugul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Scientific journals had the highest quality typology and all scientific journal web pages were high quality. Kaya & Görmez [17] and Lim et al [30] similarly found scientific journals to have the highest quality typology. In contrast, Basavakumar et al [15] and Chumber et al [28] found non-profit and health portal web pages to be of the highest quality, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Scientific journals had the highest quality typology and all scientific journal web pages were high quality. Kaya & Görmez [17] and Lim et al [30] similarly found scientific journals to have the highest quality typology. In contrast, Basavakumar et al [15] and Chumber et al [28] found non-profit and health portal web pages to be of the highest quality, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…HONcode certification requires a fiscal contribution according to the type of website and its visibility: a commercial website with high visibility costs $385 versus a non-commercial website with low visibility, which costs $65. Further, the contribution must be renewed annually when the site is reevaluated [30].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the readability of ChatGPT was evaluated using widely used Flesch Reading Ease (FRE) Score, Flesch–Kincaid grade level (FKGL), Gunning Fog Index (GFI), Coleman–Liau Index (CLI), and Simple Measure of Gobbledygook (SMOG) tools (Table 2 ) 21 . The FRE score ranges from 0 to 100; the higher the score, the easier to read the passage.…”
Section: Methodsmentioning
confidence: 99%
“…14 The JAMA scoring system was published as a suggestion for a basic quality standard for information on healthcare by Silberg et al in 1997, and it consists of four criteria with one point for each criterion and a total possible score of four points. 19,20 Similar to other quality scores discussed above, the JAMA benchmarks were widely used for evaluating the reliability and quality of the medical videos 14,19,21 Inter-rater reliability was evaluated for the three scoring systems (JAMA, GQS and DISCERN) using inter-class correlation estimates and their 95% confidence interval (inter-class correlation was >90% for all scoring systems). Variables were tested for normality using the Shapiro-Wilk test.…”
Section: Methodsmentioning
confidence: 99%
“…14 The JAMA scoring system was published as a suggestion for a basic quality standard for information on healthcare by Silberg et al in 1997, and it consists of four criteria with one point for each criterion and a total possible score of four points. 19,20 Similar to other quality scores discussed above, the JAMA benchmarks were widely used for evaluating the reliability and quality of the medical videos 14,19,21…”
Section: Methodsmentioning
confidence: 99%